2012
DOI: 10.1016/j.yjmcc.2012.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Regional mechanics determine collagen fiber structure in healing myocardial infarcts

Abstract: Following myocardial infarction, the mechanical properties of the healing infarct are an important determinant of heart function and the risk of progression to heart failure. In particular, mechanical anisotropy (having different mechanical properties in different directions) in the healing infarct can preserve pump function of the heart. Based on reports of different collagen structures and mechanical properties in various animal models, we hypothesized that differences in infarct size, shape, and/or location… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
142
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(152 citation statements)
references
References 45 publications
10
142
0
Order By: Relevance
“…We (4,14,21) and others (22) have reported a range of collagen fiber structures in healing infarcts in different animal models, and have shown that manipulating anisotropy in healing infarcts can improve left ventricular pump function (5,23). These prior studies focused on collagen content and alignment averaged over many microscopic fields; broadly, they show collagen fibers oriented in planes parallel to the epicardial surface, with a degree of overall alignment that depends strongly on the mechanical environment during scar formation (4).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We (4,14,21) and others (22) have reported a range of collagen fiber structures in healing infarcts in different animal models, and have shown that manipulating anisotropy in healing infarcts can improve left ventricular pump function (5,23). These prior studies focused on collagen content and alignment averaged over many microscopic fields; broadly, they show collagen fibers oriented in planes parallel to the epicardial surface, with a degree of overall alignment that depends strongly on the mechanical environment during scar formation (4).…”
Section: Discussionmentioning
confidence: 99%
“…We and others have quantified the collagen structure of healing myocardial infarcts and found that both collagen content and collagen fiber orientation vary widely across different experimental models (see a recent review by Richardson et al (3)). Our group proposed that differences in the average degree of structural anisotropy in healing infarcts arise from differences in regional mechanics during scar formation (4). During the course of these studies, we noticed that collagen orientation in many of the scars we examined appeared to vary significantly from region to region.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…It could also be due to the variation in the amount of isolated muscle fibres especially when considering the difficulty of precisely controlling the size of the infarct in the samples as we demonstrated in this study. Furthermore, the orientation of collagen was shown to vary according to the location of the infarct in the LV of a rat [37]; the collagen in a mid-ventricle infarct aligns mostly in the circumferential direction whereas collagen fibres are randomly oriented in an apical infarct. All or some of these factors may have contributed in the discrepancy between the two studies.…”
Section: Mechanical Properties Of Infarctsmentioning
confidence: 99%